Effects of low dose ramipril on cardiovascular and renal outcomes in patients with type 2 diabetes and raised excretion of urinary albumin: randomised, double blind, placebo controlled trial (the DIABHYCAR study). Issue 7438 (11th February 2004) - Marre, Michel; Lievre, Michel; Chatellier, Gilles; Mann, Johannes F E; Passa, Philippe; Ménard, Joël
Abstract: Objective To investigate whether a low dose of the angiotensin converting enzyme (ACE) inhibitor ramipril lowers cardiovascular and renal events in patients with type 2 diabetes who have microalbuminuria or proteinuria. Design Randomised, double blind, parallel group trial comparing ramipril (1.25 mg/day) with placebo (on top of usual treatment) for cardiovascular and renal outcomes for at least three years. Setting Multicentre, primary care study conducted mostly by general practitioners in 16 European and north African countries. Participants 4912 patients with type 2 diabetes aged > 50 years who use oral antidiabetic drugs and have persistent microalbuminuria or proteinuria (urinary albumin excretion 20 mg/l in two consecutive samples), and serum creatinine ≤ 150 μmol/l. Main outcome measures The primary outcome measure was the combined incidence of cardiovascular death, non-fatal myocardial infarction, stroke, heart failure leading to hospital admission, and end stage renal failure. Results Participants were followed for 3 to 6 (median 4) years. There were 362 primary events among the 2443 participants taking ramipril (37.8 per 1000 patient years) and 377 events among the 2469 participants taking placebo (38.8 per 1000 patient years; hazard ratio 1.03 (95% confidence interval 0.89 to 1.20, P = 0.65)). None of the components of the primary outcome was reduced. Ramipril lowered systolic and diastolic blood pressures (by 2.43 and 1.06 mm Hg respectively after two years) and favoured regression from microalbuminuria (20-200 mg/l) or proteinuria (> 200mg/l) to normal level (< 20 mg/l) or microalbuminuria (P < 0.07) in 1868 participants who completed the study. Conclusions Low dose (1.25 mg) ramipril once daily has no effect on cardiovascular and renal outcomes of patients with type 2 diabetes and albuminuria, despite a slight decrease in blood pressure and urinary albumin. The cardiovascular benefits of a daily higher dose (10 mg) ramipril observed elsewhere are not found with an eightfold lower daily dose.